Cooperative Actions of CRP-cAMP and FNR Increase the Fosfomycin Susceptibility of Enterohaemorrhagic Escherichia coli (EHEC) by Elevating the Expression of glpT and uhpT under Anaerobic Conditions - Kurabayashi, Kumiko; Tanimoto, Koichi; Tomita, Haruyoshi; Hirakawa, Hidetada (Frontiers in Microbiology, 2017)
Bacterial infections to anaerobic site are often hard to be treated because the activity of most of antimicrobials decreases under anaerobic conditions. However, fosfomycin rather provides a greater activity under anaerobic conditions than aerobic conditions. Previously, we found that expression of glpT and uhpT, fosfomycin symporters in enterohaemorrhagic Escherichia coli (EHEC) was upregulated by FNR, a global regulator during the anaerobiosis of the bacterium, which led to increased uptake and susceptibility to this drug. In this study, we showed that expression of glpT and uhpT is induced by CRP-cAMP, the regulator complex under both aerobic and anaerobic conditions. The activity of CRP-cAMP in EHEC was elevated under anaerobic conditions because levels of both CRP and cAMP were higher in the cells when grown anaerobically than those when grown aerobically. Results of expression study using mutants indicated that CRP-cAMP is indispensable for expression of glpT but not uhpT whereas that of uhpT requires UhpA that is the response regulator composing of two-component system with the sensor kinase, UhpB. The CRP-cAMP protein bound to a region that overlaps RNA polymerase binding site for glpT and region upstream of UhpA binding site for uhpT. FNR bound to a region further upstream of CRP-cAMP binding site on region upstream of the glpT gene. These combined results suggested that increased antibacterial activity of fosfomycin to EHEC under anaerobic conditions is due to activation of FNR and increment of CRP-cAMP activity. Then, FNR enhances the expression of glpT activated by CRP-cAMP while CRP-cAMP and FNR cooperatively aids the action of UhpA to express uhpT to maximum level.